Olfactory neuronal cells as a promising tool to realize the “druggable genome” approach for drug discovery in neuropsychiatric disorders - Mihaljevic, Marina; Lam, Max; Ayala-Grosso, Carlos; Davis-Batt, Finn; Schretlen, David J.; Ishizuka, Koko; Yang, Kun; Sawa, Akira (Frontiers in Neuroscience, 2023)
“Druggable genome” is a novel concept that emphasizes the importance of using the information of genome-wide genetic studies for drug discovery and development. Successful precedents of “druggable genome” have recently emerged for some disorders by combining genomic and gene expression profiles with medical and pharmacological knowledge. One of the key premises for the success is the good access to disease-relevant tissues from “living” patients in which we may observe molecular expression changes in association with symptomatic alteration. Thus, given brain biopsies are ethically and practically difficult, the application of the “druggable genome” approach is challenging for neuropsychiatric disorders. Here, to fill this gap, we propose the use of olfactory neuronal cells (ONCs) biopsied and established via nasal biopsy from living subjects. By using candidate genes that were proposed in a study in which genetic information, postmortem brain expression profiles, and pharmacological knowledge were considered for cognition in the general population, we addressed the utility of ONCs in the “druggable genome” approach by using the clinical and cell resources of an established psychosis cohort in our group. Through this pilot effort, we underscored the chloride voltage-gated channel 2 (CLCN2) gene as a possible druggable candidate for early-stage psychosis. The CLCN2 gene expression was associated with verbal memory, but not with other dimensions in cognition, nor psychiatric manifestations (positive and negative symptoms). The association between this candidate molecule and verbal memory was also confirmed at the protein level. By using ONCs from living subjects, we now provide more specific information regarding molecular expression and clinical phenotypes. The use of ONCs also provides the opportunity of validating the relationship not only at the RNA level but also protein level, leading to the potential of functional assays in the future. Taken together, we now provide evidence that supports the utility of ONCs as a tool for the “druggable genome” approach in translational psychiatry.